Hubungan Kualitas Air Denagn Kelimpahan Fitoplankton Di Segara Anakan Bagian Timur Cilacap Jawa Tengah - Hasby Ghoni Asiddiqi; Agatha Sih Piranti; Erwin Ardli Riyanto (Fakultas Biologi Universitas Jenderal Soedirman, 2019)
Phytoplankton is the primary producer whose existence depends not only on the nutrient. The eastern part of Segara Anakan waters experienced changes where the decline in quality which received input from organic and inorganic wastes and residential, industrial and factory wastes of Holcim and Pertamina factories. The purpose of this research is to study the water quality and to study the relationship between water quality and abundance of phytoplankton at the eastern part of Segara Anakan. The result showed that Water quality in Segara Anakan waters in the eastern part of Cilacap consists of several parameters that beyond the quality standards according to the Keputusan Menteri Lingkungan Hidup No. 51 of 2004 such as pH, Nitrate, Ammonia, Phosphate, and TSS. Water temperature is a physical factor which has a strong negative correlation with the abundance of phytoplankton, followed by TSS as a physical factor which has a positive correlation. The chemical factor which has a positive correlation with abundance are TDS, Nitrite and pH, followed by Phosphate, Salinity, Ammonia, and Nitrate which has a negative correlation with the abundance of phytoplankton. Key Words: Environmental factor, phytoplankton, Segara Anakan, Spatial variation, temporal variation.